Analisis Faktor Yang Mempengaruhi Persepsi Perawat Tentang Pelaksanaan Supervisi - Suhartini, Titik (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Perception is a factor that greatly determines the formation of individual attitudes or behavior, so that it is something meaningful. The implementation of health services is seen as having an important role. To be able to improve the health status of the community, many things need to be done. What is meant by health service is every effort that is carried out individually or jointly in an organization to maintain and improve health, prevent and cure disease and restore the health of individuals, families, groups and or communities.Hospitals in the Probolinggo district consist of regional and private ownership. There are 2 local government hospitals and 4 privately owned hospitals and clinics. The management of hospitals owned by the regional government is under the responsibility of the head of the regional government. This study aims to analyze the factors that influence nurses' perceptions about the implementation of supervision at home in the Probolinggo Regency area.Methods: This study uses a correlational analytical research design with a cross sectional approach. The population is all nurses who are in the inpatient ward of a hospital in Probolinggo Regency with samples that meet the research criteria, namely nurses who are cooperative and willing to be respondents. The sampling technique used is purposive sampling with a sample of 89 respondents. Analysis was carried out by logistic regression to determine the most dominant factor with a significance level of p 0.05Results: The results of the analysis show that the most related to the implementation of supervision is supervisory competence because it has the largest OR value of 28.7, meaning that a supervisory competence that is carried out well has a 28.7 chance of producing good supervision after being controlled by supervision techniques, supervision principles, activities routines and supervision models.Conclusion: Direct supervision allows nursing managers to find various obstacles/problems in the implementation of nursing care in the room by trying to look at it as a wholeÂ